Access to resources in forest-rich and forest-poor contexts - Porro R.; Tiani, A.M.; Tchikangwa, B.; Sardjono, M.A.; Salim, A.; Colfer, C.J.P.; Brocklesby, M.A. (Resources for the Future and Center for International Forestry Research, 2001)
This chapter examines the results from two pebble sorting methods designed to help assess important elements of human well-being, relating to access to resources and benefits from the forest (both intra and intergenerationally). The two methods were conducted in forest rich and forest poor sites in Indonesia, Cameroon and Brazil – described in detail in Annex 2 of the Introduction. Our hypotheses were a) that inequitable sharing of benefits (as perceived by local stakeholders) correlates with poor forest quality, and b) that people’s perceptions of access to resources by their grandparents, themselves and their grandchildren would reflect forest quality in their area. Instead, it was found that patterned similarities, both in intra and intergenerational sharing of benefits, were more likely to be based on regional differences than on forest quality differences.